A genome-wide association study on hematopoietic stem cell transplantation reveals novel genomic loci associated with transplant outcomes - Rosenberger, Albert; Crossland, Rachel E.; Dressel, Ralf; Kube, Dieter; Wolff, Daniel; Wulf, Gerald; Bickeböller, Heike; Dickinson, Anne; Holler, Ernst (Frontiers in Immunology, 2024)
Introduction: Data on genomic susceptibility for adverse outcomes after hematopoietic stem cell transplantation (HSCT) for recipients are scarce. Methods: We performed a genome wide association study (GWAS) to identify genes associated with survival/mortality, relapse, and severe graft-versus-host disease (sGvHD), fitting proportional hazard and subdistributional models to data of n=1,392 recipients of European ancestry from three centres. Results: The single nucleotide polymorphism (SNP) rs17154454, intronic to the neuronal growth guidant semaphorin 3C gene (SEMA3C), was genomewide significantly associated with event-free survival (p=7.0x10 -8 ) and sGvHD (p=7.5x10 -8 ). Further associations were detected for SNPs in the Paxillin gene (PXN) with death without prior relapse or sGvHD , as well as for SNPs of the Plasmacytoma Variant Translocation 1 gene (PVT1, a long non-coding RNA gene), the Melanocortin 5 Receptor (MC5R) gene and the WW Domain Containing Oxidoreductase gene (WWOX), all associated with the occurrence of sGvHD. Functional considerations support the observed associations. Discussion: Thus, new genes were identified, potentially influencing the outcome of HSCT.